2005
DOI: 10.1159/000082580
|View full text |Cite
|
Sign up to set email alerts
|

Peanut Protein Allergens: The Effect of Roasting on Solubility and Allergenicity

Abstract: Background: A contributing factor to food allergen stability is heat resistance. Peanut allergens in particular are resistant to heat, which results in their decreased solubility upon routine extraction and may have a profound influence on their continued presence in the digestive tract. Although there have been a number of studies characterizing soluble extracts of raw and roasted proteins, the relative solubility of the insoluble material following routine extraction for residual allergen characterization ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 29 publications
5
46
0
Order By: Relevance
“…RP was selected in this study because it has been recognized that it is more allergenic than raw peanut [17,18,19,20,21,22]. RP extract binds IgE from patients with peanut allergy at approximately 90-fold higher levels than that of raw peanuts, and the protein modifications induced by the Maillard reaction contribute to the observed effect [17,20,21.…”
Section: Discussionmentioning
confidence: 99%
“…RP was selected in this study because it has been recognized that it is more allergenic than raw peanut [17,18,19,20,21,22]. RP extract binds IgE from patients with peanut allergy at approximately 90-fold higher levels than that of raw peanuts, and the protein modifications induced by the Maillard reaction contribute to the observed effect [17,20,21.…”
Section: Discussionmentioning
confidence: 99%
“…Like peanut protein allergens bhetki and mackerel allergens were found to be resistant to thermal denaturation. This indicated that conformational epitopes may not always be vital and play a minor role in their allergenicity [11]. Also it may be possible that the epitopes are present at the sites of the protein that are not heat-sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that different forms of heat affected the allergenicity in different ways. While roasting increased the allergenicity of peanut protein or left it unaltered, Ara h 1, boiling or frying reduced its allergenic potential [11]. There are reports that the IgE-binding capacity of the allergen increased relatively on storage due to the formation of new peptides [12].…”
Section: Introductionmentioning
confidence: 99%
“…A finding that the roasting process reduces peanut protein solubility [33] will be used to compare the in vivo digestion of raw and processed peanut under similar physiological conditions in future studies. Reduced solubility could increase the amount of surviving particulate material available for transport through the stomach and into the small intestine for antigen sampling in the GI mucosa.…”
Section: Discussionmentioning
confidence: 99%